The transformative capacity of new technologies. How innovations affect sectoral change: Conceptual considerations - Ulrich Dolata (Max Planck Institute for the Study of Societies, 2008)
Following up on recent debates about sectoral systems of innovation and production, the paper introduces a heuristic framework for analyzing and explaining distinct patterns of technology-based sectoral change. The concept is based on two interrelated influencing factors. The first is the sectoral-specific transformative capacity of new technologies themselves, that is, their substantial or incremental impact on socioeconomic and institutional change in a given sectoral system. The second is the sectoral adaptability of socioeconomic structures, institutions, and actors confronted with the opportunities presented by new technologies. The first factor the sectoral transformative capacity of new technologies enables us to identify the technology-driven pressure to change and adjust the structural and institutional architectures of the sectoral system. The second, complementary factor sectoral adaptability helps us to discern the distinct social patterns of anticipating and absorbing this technology-based pressure. The specific interplay between the two influencing factors creates distinguishable modes of sectoral transformation, ranging from anticipative and smooth adjustments to reactive and crisis-ridden patterns of change. Even processes of radical sectoral change continue over longer periods of mismatch, characterized by a cumulation of numerous and mostly gradual organizational, structural, and institutional transformations.
Keywords: 300; Innovationsdiffusion; Technischer Fortschritt; Strukturwandel; Theorie